Lobar Hepatocellular Carcinoma with Ipsilateral Portal Vein Tumor Thrombosis Treated with Yttrium-90 Glass Microsphere Radioembolization: Preliminary Results - M. Pracht; J. Edeline; L. Lenoir; M. Latournerie; H. Mesbah; O. Audrain; Y. Rolland; B. Clément; J. L. Raoul; E. Garin; E. Boucher (International Journal of Hepatology)
Portal vein tumor thrombosis (PVTT) is a common complication of hepatocellular carcinoma (HCC) and has a negative impact on prognosis. This characteristic feature led to the rationale of the present trial designed to assess the efficacy and the safety of yttrium-90 glass-microsphere treatment for advanced-stage lobar HCC with ipsilateral PVTT. 18 patients with unresectable lobar HCC and ipsilateral PVTT were treated in our institution with 90Y-microS radioembolization. Patients were evaluated every 3 to 6 months for response, survival, and toxicity. Mean follow-up was 13.0 months (2.2–50.6). Outcomes were: complete response (n=2), partial response (n=13), stable disease (n=1), and progressive disease (n=2) giving a disease control rate of 88.9%. Four patients were downstaged. Treating lobar hepatocellular carcinoma with ipsilateral portal vein thrombosis with yttrium-90 glass-microsphere radioembolization is safe and efficacious. Further clinical trials are warranted to confirm these results and to compare 90Y-microS with sorafenib, taking into account not only survival but also the possibility of secondary surgery for putative curative intention after downstaging.